USING HISTORICAL ART AND MONUMENTS TO ENHANCE CREATIVE THINKING IN SCHOOL STUDENTS - Rustamova Farangiz Asqarbek qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines pedagogical strategies for fostering creative thinking in school students through engagement with historical art and monuments. It explores the use of visual art and heritage sites as educational tools to develop imagination, critical analysis, and aesthetic sensitivity. The study highlights methods for incorporating historical works into classroom activities, enabling students to interpret, analyze, and creatively express historical and cultural concepts. Findings suggest that historical art and monuments significantly enhance students’ visual literacy, artistic expression, and historical understanding. Practical recommendations are provided for educators seeking to integrate creative and historical learning in school curricula.